Verbal aggression: linguistic and legal aspect - Yelnikova, N. I.; Єльнікова, Н. І.; Yushkevych, O. H.; Юшкевич, О. Г.; Юшкевич Олена Геннадіївна (Право і безпека. – 2025. – № 2 (97). – С. 17-26, 2025)
The article examines the phenomenon of verbal aggression as a linguistic and legal problem which, under certain conditions, can be qualified as an administrative or criminal offence. The verbal aggression is defined as a conscious communicative strategy aimed at achieving certain goals through the use of language. Theoretical aspects of communication strategies are characterised. The key characteristics, forms of manifestation and consequences of verbal aggression in the context of interpersonal communication are analysed. Various forms of verbal aggression are considered, including insults, threats, criticism, irony, manipulation and ignoring. Particular attention is paid to the analysis of linguistic means used to implement verbal aggression as a communication strategy. The lexical, syntactic and stylistic features of aggressive statements, as well as their impact on the emotional state of the interlocutor are identified. The term “offence committed verbally” in the context of legal linguistics is considered, and its difference from more established concepts such as “hate speech” or “verbal aggression” is emphasised. It is noted that the development of jurisprudence contributes to a detailed analysis of speech actions that may have legal significance. The main attention is paid to the characterization of offences committed verbally through the components of their legal qualification, in particular, the object, objective side, subject and subjective side. The public danger associated with their information impact on public relations, in particular, human rights, public order, state security and interests of justice, is considered. The linguistic expertise is analysed as an important tool for determining legally significant statements. The article also deals with the issues of enshrining verbal offences in the criminal and administrative legislation of Ukraine. Examples of articles of the Criminal Code of Ukraine and the Code of Ukraine on Administrative Offences regulating liability for aggressive speech acts, including threats, harassment and calls for offences, are provided. It is noted that an important aspect of law enforcement is to take into account the context of statements, their content and possible consequences. The importance of further development of interdisciplinary approaches to the analysis of verbal offences is emphasised, which will allow for a more effective classification of such acts according to their semantic model. The emphasis is placed on the need to systematically consolidate the concept of ‘verbally committed offence’ in legal and scientific doctrine to ensure an adequate legal assessment of such phenomena.

Досліджено феномен вербальної агресії як лінгвістично-правову проблему, яку за певних умов можна кваліфікувати як адміністративне або кримінальне правопорушення. Вербальну агресію визначено як свідому комунікативну стратегію, спрямовану на досягнення певних цілей шляхом використання мовних засобів. Охарактеризовано теоретичні аспекти комунікативних стратегій. Проаналізовано основні характеристики, форми прояву та наслідки вербальної агресії в контексті міжособистісного спілкування. Розглянуто різновиди вербальної агресії, зокрема образи, погрози, критику, іронію, маніпуляції та ігнорування. Особливу увагу приділено аналізу мовних засобів, що використовуються для реалізації вербальної агресії як комунікативної стратегії. Визначено лексичні, синтаксичні та стилістичні особливості агресивних висловлювань, а також їхній вплив на емоційний стан співрозмовника. Розглянуто термін «правопорушення, вчинене вербально» у контексті юридичної лінгвістики, наголошено на його відмінності від більш усталених понять, таких як «мова ворожнечі» чи «вербальна агресія». Зазначено, що розвиток юридичної лінгвістики сприяє детальному аналізу мовленнєвих дій, які можуть мати юридичне значення. Основну увагу зосереджено на характеристиці правопорушень, учинених вербально, через аналіз елементів їх правової кваліфікації, зокрема об’єкта, об’єктивної сторони, суб’єкта та суб’єктивної сторони. Розглянуто їхню суспільну небезпеку, що пов’язана з інформаційним впливом на суспільні відносини, зокрема на права особи, громадський порядок, державну безпеку та інтереси правосуддя. Проаналізовано лінгвістичну експертизу як важливий інструмент для встановлення юридично значущих висловлювань. Висвітлено питання нормативного закріплення правопорушень, учинених вербально, у кримінальному та адміністративному законодавстві України. Наведено приклади статей Кримінального кодексу України та Кодексу України про адміністративні правопорушення, які регулюють відповідальність за агресивні мовленнєві акти, зокрема погрози, цькування та заклики до вчинення правопорушень. Зазначено, що важливим аспектом правозастосування є врахування контексту висловлювань, їхнього змісту та можливих наслідків. Наголошено на необхідності подальшого розвитку міждисциплінарних підходів до аналізу правопорушень, учинених вербально, що дасть змогу ефективніше класифікувати такі діяння за їхньою смисловою моделлю. Акцентовано на потребі системного закріплення поняття «правопорушення, учинене вербально» у правовій та науковій доктрині задля забезпечення адекватної юридичної оцінки подібних явищ.
Вербальна агресія: лінгвістично-правовий аспект
Keywords: verbal aggression; legal linguistics; crime; offence; violence; harassment; legal responsibility; вербальна агресія; юридична лінгвістика; злочин; правопорушення; насильство; цькування; юридична відповідальність